Ternary positive electrode material and preparation method thereof
Through the ternary positive electrode material of zirconium, aluminum double-doped, CQDs and nano CaCO3 coating layers, the performance problems of nickel-cobalt-manganese materials at cycling, high and low temperatures are solved, and the overall performance of lithium-ion batteries is improved.
Patent Information
- Application Number
- CN202411370130.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-29
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2044-09-29
AI Technical Summary
The structure of nickel-cobalt-manganese ternary cathode material is prone to change during cyclic charging and discharging, resulting in rapid capacity degradation, prone to failure at high temperatures, and low-temperature power performance needs to be optimized.
The ternary cathode material with double doping of zirconium and aluminum is coated with CQDs and nano CaCO3 layers on its surface to enhance the structural stability and conductivity of the material and inhibit the growth of lithium dendrites.
It significantly improves the low-temperature power, high-temperature storage and cycling performance of ternary lithium-ion batteries.
Smart Images

Figure CN119275265A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of lithium ion batteries, and in particular relates to a ternary positive electrode material and a preparation method thereof. Background Art
[0002] The development of new energy vehicles is a powerful measure for my country to seek new economic growth points and promote industrial transformation and upgrading. More importantly, new energy vehicles are in line with the current trend of green travel and will help the international community strive to achieve the goal of carbon neutrality. Among them, the cruising range of a car is an important factor in whether it can be quickly and widely popularized, and this depends to a large extent on the energy density of the positive electrode material of lithium-ion batteries. In recent years, nickel-cobalt-manganese ternary positive electrode materials have been favored by many car companies due to their advantages of high capacity and high voltage, and have become the development focus of the industry at this stage. However, there are some common problems with nickel-cobalt-manganese ternary materials that need to be solved urgently. First: ternary materials have high voltage and energy storage capacity, and are prone to structural evolution during cyclic charging and discharging, resulting in rapid degradation of capacity; second: ternary lithium batteries are prone to degradation and failure at high temperatures, and their power performance at low temperatures still needs to be further optimized. Summary of the invention
[0003] In view of the deficiencies in the prior art, the object of the present invention is to provide a high-performance ternary positive electrode material, which has good electronic conductivity and can effectively inhibit the growth of lithium dendrites, while enhancing the structural stability of the material through doping modification, thereby improving the low-temperature power, high-temperature storage and cycle performance of the ternary lithium-ion battery.
[0004] The ternary positive electrode material provided by the present invention comprises a zirconium and aluminum dual-doped ternary positive electrode material located in the inner core and a CQDs coating layer and a nano-CaCO3 coating layer sequentially coated on the surface of the zirconium and aluminum dual-doped ternary positive electrode material from the inside to the outside.
[0005] The ternary material is bulk-doped with zirconium and aluminum to enhance the structural stability of the material. The CQDs coating has excellent conductivity and can improve the transmission efficiency of electrons and lithium ions, thereby improving the low-temperature power performance of the ternary battery cell. The nano-CaCO3 coating can stabilize the crystal structure of the ternary material. At the same time, nano-CaCO3 can continuously adsorb the by-product HF of the electrolyte, inhibit the acidification of the electrolyte at high temperature, and avoid the growth of lithium dendrites caused by acidity, thereby improving the high-temperature storage and cycle performance of the ternary lithium-ion battery.
[0006] The molecular formula of the ternary positive electrode material in the zirconium and aluminum dual-doped ternary positive electrode material is LiNi 0.7 Co 0.1 Mn 0.2 O2; The mass of the CQDs coating layer is 0.01%-0.05% of the mass of the zirconium and aluminum dual-doped ternary positive electrode material, and the mass of the nano-CaCO3 coating layer is 0.05%-0.15% of the mass of the zirconium and aluminum dual-doped ternary positive electrode material.
[0007] The above-mentioned ternary positive electrode material is prepared by a method comprising the following steps: 1) Preparation of zirconium and aluminum dual-doped ternary cathode material: mixing the ternary precursor with lithium carbonate, zirconium source and aluminum source, and then sintering the mixed material in an oxygen atmosphere, and crushing it after sintering to obtain the zirconium and aluminum dual-doped ternary cathode material; 2) Preparation of CQDs coating layer: The zirconium and aluminum dual-doped ternary cathode material prepared in step 1) is mixed with ethylene glycol (CH2OH)2 according to a mass ratio and stirred continuously, and the resulting solution is transferred to a reactor, heated, and kept warm to obtain a ternary cathode material with CQDs coated on the surface; 3) Preparation of nano-CaCO3 coating layer: After uniformly mixing the product obtained in step 2) with nano-CaCO3, the mixture is sintered in an oxygen atmosphere to obtain a ternary positive electrode material with a double-doping and double-coating structure.
[0008] In step 1) of the above method, the molecular formula of the ternary precursor is: Ni 0.7 Co 0.1 Mn 0.2 (OH)2; The zirconium source may be at least one of zirconium oxide and zirconium hydroxide; The aluminum source may be at least one of aluminum oxide, aluminum hydroxide, The amount of zirconium added is 0.1%-0.3% of the mass of the ternary precursor; The amount of aluminum added is 0.05%-0.15% of the mass of the ternary precursor; The ratio of the total molar number of metals in the ternary precursor to the molar number of Li in lithium carbonate is 1:1.02-1.069; The sintering conditions are 900-930°C and the time is 10-20h; During the sintering process, oxygen with a purity of more than 95% is introduced; In step 2) of the above method, the mass ratio of the ethylene glycol (CH2OH)2 to the zirconium and aluminum dual-doped ternary positive electrode material obtained in step 1) can be: 1:2-6; The continuous stirring time may be 1-3h; The heating temperature can be 160-240℃, and the insulation time can be 4-6h; Step 2) also includes cooling the reaction system to room temperature after heat preservation, centrifuging, washing, and vacuum drying the precipitate, wherein the vacuum drying temperature can be 100-120° C. and the time can be 4-8 hours.
[0009] In step 3) of the above method, the amount of the nano-CaCO3 added is 0.05-0.15% of the mass of the ternary positive electrode material obtained in step 2); The sintering temperature is 600-700°C and the sintering time is 4-6h; Step 3) also includes the operations of crushing, screening and demagnetizing the sintered product to obtain the final product.
[0010] The application of the above-mentioned ternary positive electrode material in lithium-ion batteries also falls within the protection scope of the present invention.
[0011] The present invention also provides a lithium ion battery, wherein the positive electrode of the lithium ion battery is made from the above-mentioned ternary positive electrode material.
[0012] The present invention also provides an electrical device, wherein the electrical device contains the lithium ion battery.
[0013] Compared with the prior art, the present invention has the following beneficial effects: The ternary positive electrode material with a double-doping and double-coating structure prepared by the present invention has excellent low-temperature power performance, and also has good high-temperature storage and cycle performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0014] Figure 1 The low temperature power performance diagram of four groups of battery cells; Figure 2 This is a graph of high temperature storage performance of four groups of batteries; Figure 3 This is the high temperature cycle performance diagram of four groups of battery cells; Figure 4 This is a scanning electron microscope image of the ternary positive electrode material prepared in Example 4 of the present invention. DETAILED DESCRIPTION
[0015] The present invention is further described in detail below in conjunction with specific embodiments, and the examples provided are only for illustrating the present invention, rather than for limiting the scope of the present invention. The examples provided below can be used as a guide for further improvements by those of ordinary skill in the art, and do not constitute a limitation of the present invention in any way.
[0016] The experimental methods in the following examples, unless otherwise specified, are all conventional methods, and are performed according to the techniques or conditions described in the literature in the field or according to the product instructions. The materials, reagents, etc. used in the following examples, unless otherwise specified, can all be obtained from commercial channels.
[0017] Example 1 A method for preparing a high-performance ternary cathode material comprises the following steps: S1. Preparation of zirconium and aluminum dual-doped ternary positive electrode materials: The ternary precursor (Ni 0.7 Co 0.1 Mn 0.2 (OH)2) is mixed with lithium carbonate, zirconium oxide and aluminum oxide, the molar ratio of the ternary material precursor to lithium carbonate (the ratio of the total molar number of metals in the ternary precursor to the molar number of Li in the lithium carbonate) is 1:1.04, the amount of zirconium added accounts for 0.2% of the mass of the ternary precursor, and the amount of aluminum added accounts for 0.1% of the mass of the ternary precursor; then the mixed material is sent to a 915°C sintering furnace for calcination for 15 hours, oxygen with a purity of more than 95% is introduced during the sintering process, and crushed after sintering to obtain a zirconium and aluminum dual-doped ternary positive electrode material; S2. Preparation of CQDs coating layer: Ethylene glycol (CH2OH)2 and the ternary cathode material prepared by S1 were mixed in a mass ratio of 1:2 and stirred continuously for 3 hours. The uniformly mixed solution was transferred to a reactor, heated to 200°C, kept warm for 5 hours, cooled to room temperature, centrifuged, washed, and the precipitate was vacuum dried at 100°C for 6 hours to obtain a ternary cathode material with CQDs coated on the surface; S3. Preparation of nano-CaCO3 coating layer: After the product obtained in step S2 is uniformly mixed with nano-CaCO3, the mixture is sent to a sintering furnace at 700°C and calcined for 5 hours, and oxygen is introduced into the furnace during sintering; finally, the sintered material is crushed, sieved, and demagnetized to obtain the final product, that is, a ternary positive electrode material with a double-doped and double-coated structure; wherein the addition amount of nano-CaCO3 accounts for 0.15% of the ternary positive electrode material obtained in S2.
[0018] Example 2 A method for preparing a high-performance ternary cathode material comprises the following steps: S1. Preparation of zirconium and aluminum dual-doped ternary positive electrode materials: The ternary precursor (Ni 0.7 Co 0.1 Mn 0.2(OH)2) is mixed with lithium carbonate, zirconium oxide and aluminum oxide, the molar ratio of the ternary material precursor to lithium carbonate (the ratio of the total molar number of metals in the ternary precursor to the molar number of Li in the lithium carbonate) is 1:1.04, the amount of zirconium added accounts for 0.2% of the mass of the ternary precursor, and the amount of aluminum added accounts for 0.1% of the mass of the ternary precursor; then the mixed material is sent to a 915°C sintering furnace for calcination for 15 hours, oxygen with a purity of more than 95% is introduced during the sintering process, and crushed after sintering to obtain a zirconium and aluminum dual-doped ternary positive electrode material; S2. Preparation of CQDs coating layer: Ethylene glycol (CH2OH)2 and the ternary cathode material prepared by S1 were mixed in a mass ratio of 1:4 and stirred continuously for 3 hours. The uniformly mixed solution was transferred to a reactor, heated to 200°C, kept warm for 5 hours, cooled to room temperature, centrifuged, washed, and the precipitate was vacuum dried at 100°C for 6 hours to obtain a ternary cathode material with CQDs coated on the surface; S3. Preparation of nano-CaCO3 coating layer: After the product obtained in step S2 is uniformly mixed with nano-CaCO3, the mixture is sent to a sintering furnace at 700°C and calcined for 5 hours, and oxygen is introduced into the furnace during sintering; finally, the sintered material is crushed, sieved, and demagnetized to obtain the final product, that is, a ternary positive electrode material with a double-doped and double-coated structure; wherein the addition amount of nano-CaCO3 accounts for 0.15% of the ternary positive electrode material obtained in S2.
[0019] Example 3 A method for preparing a high-performance ternary cathode material comprises the following steps: S1. Preparation of zirconium and aluminum dual-doped ternary positive electrode materials: The ternary precursor (Ni 0.7 Co 0.1 Mn 0.2 (OH)2) is mixed with lithium carbonate, zirconium oxide and aluminum oxide, the molar ratio of the ternary material precursor to lithium carbonate (the ratio of the total molar number of metals in the ternary precursor to the molar number of Li in the lithium carbonate) is 1:1.04, the amount of zirconium added accounts for 0.2% of the mass of the ternary precursor, and the amount of aluminum added accounts for 0.1% of the mass of the ternary precursor; then the mixed material is sent to a 915°C sintering furnace for calcination for 15 hours, oxygen with a purity of more than 95% is introduced during the sintering process, and crushed after sintering to obtain a zirconium and aluminum dual-doped ternary positive electrode material; S2. Preparation of CQDs coating layer: Ethylene glycol (CH2OH)2 and the ternary cathode material prepared by S1 were mixed in a mass ratio of 1:2 and stirred continuously for 3 hours. The uniformly mixed solution was transferred to a reactor, heated to 200°C, kept warm for 5 hours, cooled to room temperature, centrifuged, washed, and the precipitate was vacuum dried at 100°C for 6 hours to obtain a ternary cathode material with CQDs coated on the surface; S3. Preparation of nano-CaCO3 coating layer: After the product obtained in step S2 is uniformly mixed with nano-CaCO3, the mixture is sent to a sintering furnace at 650°C and calcined for 5 hours, and oxygen is introduced into the furnace during sintering; finally, the sintered material is crushed, sieved, and demagnetized to obtain the final product, that is, a ternary positive electrode material with a double-doped and double-coated structure; wherein the addition amount of nano-CaCO3 accounts for 0.15% of the ternary positive electrode material obtained in S2.
[0020] Example 4 A method for preparing a high-performance ternary cathode material comprises the following steps: S1. Preparation of zirconium and aluminum dual-doped ternary positive electrode materials: The ternary precursor (Ni 0.7 Co 0.1 Mn 0.2 (OH)2) is mixed with lithium carbonate, zirconium oxide and aluminum oxide, the molar ratio of the ternary material precursor to lithium carbonate (the ratio of the total molar number of metals in the ternary precursor to the molar number of Li in the lithium carbonate) is 1:1.04, the amount of zirconium added accounts for 0.2% of the mass of the ternary precursor, and the amount of aluminum added accounts for 0.1% of the mass of the ternary precursor; then the mixed material is sent to a 915°C sintering furnace for calcination for 15 hours, oxygen with a purity of more than 95% is introduced during the sintering process, and crushed after sintering to obtain a zirconium and aluminum dual-doped ternary positive electrode material; S2. Preparation of CQDs coating layer: Ethylene glycol (CH2OH)2 and the ternary cathode material prepared by S1 were mixed in a mass ratio of 1:2 and stirred continuously for 3 hours. The uniformly mixed solution was transferred to a reactor, heated to 200°C, kept warm for 5 hours, cooled to room temperature, centrifuged, washed, and the precipitate was vacuum dried at 100°C for 6 hours to obtain a ternary cathode material with CQDs coated on the surface; S3. Preparation of nano-CaCO3 coating layer: After the product obtained in step S2 is uniformly mixed with nano-CaCO3, the mixture is sent to a sintering furnace at 650°C and calcined for 5 hours, and oxygen is introduced into the furnace during sintering; finally, the sintered material is crushed, sieved, and demagnetized to obtain the final product, that is, a ternary positive electrode material with a double-doped and double-coated structure; wherein the addition amount of nano-CaCO3 accounts for 0.1% of the ternary positive electrode material obtained in S2.
[0021] Figure 4 This is a scanning electron microscope image of the prepared ternary positive electrode material.
[0022] The undoped ternary cathode material is sample A0 (the ternary precursor (Ni 0.7 Co 0.1 Mn 0.2 (OH)2) is mixed with lithium carbonate, and the molar ratio of the ternary material precursor to lithium carbonate (the ratio of the total molar number of metals in the ternary precursor to the molar number of Li in the lithium carbonate) is 1:1.04; the mixed material is then sent to a 915°C sintering furnace for calcination for 15 hours, and oxygen with a purity of more than 95% is introduced during the sintering process. After the sintering is completed, it is crushed to obtain a ternary positive electrode material), and the ternary positive electrode material that is not coated but double-doped is sample A1 (the ternary precursor (Ni 0.7 Co 0.1 Mn 0.2 (OH)2) is mixed with lithium carbonate, zirconium oxide and aluminum oxide, the molar ratio of the ternary material precursor to lithium carbonate (the ratio of the total molar number of metals in the ternary precursor to the molar number of Li in the lithium carbonate) is 1:1.04, the amount of zirconium added accounts for 0.2% of the mass of the ternary precursor, and the amount of aluminum added accounts for 0.1% of the mass of the ternary precursor; the mixed materials are then sent to a 915°C sintering furnace for calcination for 15h, and oxygen with a purity of more than 95% is introduced during the sintering process. After the sintering is completed, the materials are crushed to obtain a zirconium and aluminum dual-doped ternary positive electrode material), and the dual-doped and single-coated CQDs ternary positive electrode material is sample A2 (the ternary precursor (Ni 0.7 Co 0.1 Mn 0.2(OH)2) is mixed with lithium carbonate, zirconium oxide and aluminum oxide, the molar ratio of the ternary material precursor to lithium carbonate (the ratio of the total molar number of metals in the ternary precursor to the molar number of Li in the lithium carbonate) is 1:1.04, the added amount of zirconium element accounts for 0.2% of the mass of the ternary precursor, and the added amount of aluminum element accounts for 0.1% of the mass of the ternary precursor; then the mixed material is sent to a 915℃ sintering furnace for calcination for 15h, and oxygen with a purity of more than 95% is introduced during the sintering process. After the sintering is completed, it is crushed to obtain a zirconium and aluminum dual-doped ternary positive electrode material; ethylene glycol (CH2OH)2 is mixed with the prepared ternary positive electrode material in a mass ratio of 1:2 and continuously stirred for 3h, the mixed solution is transferred to a reactor, heated to 200℃, kept warm for 5h, cooled to room temperature, centrifuged and washed, and the precipitate is The mixture was dried at 100 °C under vacuum for 6 h to obtain a ternary positive electrode material with CQDs coated on the surface). The double-doped and double-coated ternary positive electrode material prepared in Example 4 was used as sample A3. Under the same proportion of active substances, samples A0, A1, A2 and A3 were used to prepare corresponding ternary lithium-ion batteries (the positive electrode was slurried according to NCM:CNTs:PVDF=98:1:1, the positive electrode was coated with a double-sided surface density of 331.6 g / m2, and the positive electrode was rolled and compacted to 3.5 g / cc; the negative electrode was slurried according to graphite:SP:CMC:SBR=96.2:0.8:1.2:1.8, the negative electrode was coated with a double-sided surface density of 216 g / m2, and the negative electrode was rolled and compacted to 1.6 g / cc; Xinzhoubang E8A high-voltage electrolyte and Enjie 9+2+2+1+1 type separator were used). The four groups of lithium-ion batteries have the same materials, dosage, and battery preparation methods except for the positive electrode materials. The following are the test results of the performance of the four groups of batteries: (1) Battery low temperature power performance test The specific test method is: take four groups of batteries and charge them from 2.8V to 4.35V at 0.33C at 25℃, keep charging at 4.35V, and cut off current 0.05C; then discharge them to 2.8V at 0.33C for three cycles, and take the average of the three-week discharge capacity as the battery capacity C0; adjust the battery to 20% SOC at 25℃ according to the C0 value, then place the battery at -25℃ for 10h, and discharge at 1.1C for 30S. The test results are shown in Table 1. Figure 1 .
[0023] Table 1 -25℃ low temperature DCR performance of four groups of cells
[0024] From Table 1 and Figure 1It can be seen that the dual-doping modification can reduce the low-temperature DCR of the ternary material. The introduction of the CQDs coating layer on the basis of dual-doping can significantly reduce the low-temperature DCR of the ternary material. After coating with nano-CaCO3, the low-temperature DCR performance of the ternary material can remain unchanged. This shows that the low-temperature power performance of the battery is greatly improved when the dual-doping and dual-coating structure of the ternary cathode material prepared by the present invention is applied to lithium-ion batteries. (The lower the low-temperature DCR value of the battery cell, the better its low-temperature power performance) (2) Battery high temperature storage performance test The specific test method is: take four groups of batteries and charge them from 2.8V to 4.35V at 1C at 25℃, keep charging at 4.35V, and cut off the current at 0.05C; then discharge them to 2.8V at 1C constant current for three cycles, and take the average of the three-week discharge capacity as the initial capacity C0 of the battery; charge the battery to full power at 1C and place it in a 60℃ constant temperature box for 7 days, and resume charging and discharging for 3 times at 25℃. The test results are shown in Table 2 and Figure 2 .
[0025] Table 2 High shelf capacity retention rate and recovery rate (mean) of four groups of batteries
[0026] From Table 2 and Figure 2 It can be seen that dual-doping modification and single-coating CQDs can slightly improve the high-temperature storage performance of the ternary material. On this basis, the high-temperature storage performance of the ternary material is significantly improved after the introduction of the nano-CaCO3 coating layer; this shows that the dual-doping and dual-coating structured ternary positive electrode material prepared by the present invention is applied to lithium-ion batteries, and the high-temperature storage performance of the battery is greatly improved.
[0027] (3) Battery high temperature cycle performance test The specific test method is: take four groups of batteries and charge them from 2.8V to 4.35V at a constant current of 0.5C, maintain a constant voltage of 4.35V, and cut off the current at 0.05C; then discharge them to 2.8V at a constant current of 1C, and cycle the charge and discharge for 2000 cycles. The test results are shown in Table 3. Figure 3 shown.
[0028] From Table 3 and Figure 3It can be seen that after 380 cycles of the A0 sample, the capacity retention rate has dropped to about 87%; the cycle performance of the ternary material can be slightly improved after dual doping modification, the battery cycle 546 weeks, the capacity retention rate is about 85.7%; the introduction of the CQDs coating layer on the basis of dual doping can significantly improve the high-cycle performance of the material, the high-cycle life of the battery cell is about 860 weeks; after coating with nano-CaCO3, the high-cycle performance of the ternary material is further improved, the cycle 937 weeks, the capacity retention rate is still above 80%; this shows that the dual-doped and dual-coated ternary positive electrode material prepared by the present invention is applied to lithium-ion batteries, and the high-temperature cycle performance of the battery is also significantly improved.
[0029] Table 3 High temperature cycle capacity retention rate of four groups of batteries
[0030] In summary, the ternary positive electrode material with a dual-doping and dual-coating structure prepared in the present invention has excellent low-temperature power performance, as well as good high-temperature storage and cycle performance.
[0031] The present invention has been described in detail above. For those skilled in the art, without departing from the purpose and scope of the present invention, and without the need to carry out unnecessary experimental conditions, the present invention can be implemented in a wide range under equivalent parameters, concentrations and conditions. Although the present invention provides specific embodiments, it should be understood that the present invention can be further improved. In a word, according to the principles of the present invention, the application is intended to include any changes, uses or improvements to the present invention, including departure from the disclosed scope in the application, and changes made with conventional techniques known in the art.
Claims
1. A ternary positive electrode material, characterized in that: The ternary positive electrode material comprises a zirconium and aluminum dual-doped ternary positive electrode material located in the inner core and a CQDs coating layer and a nano-CaCO3 coating layer sequentially coated on the surface of the zirconium and aluminum dual-doped ternary positive electrode material from the inside to the outside.
2. The ternary positive electrode material according to claim 1, characterized in that: The mass of the CQDs coating layer is 0.01%-0.05% of the mass of the zirconium and aluminum dual-doped ternary positive electrode material, and the mass of the nano-CaCO3 coating layer is 0.05%-0.15% of the mass of the zirconium and aluminum dual-doped ternary positive electrode material.
3. A method for preparing the ternary cathode material according to claim 1 or 2, comprising the following steps: 1) Preparation of zirconium and aluminum dual-doped ternary cathode material: mixing the ternary precursor with lithium carbonate, zirconium source and aluminum source, and then sintering the mixed material in an oxygen atmosphere, and crushing it after sintering to obtain the zirconium and aluminum dual-doped ternary cathode material; 2) Preparation of CQDs coating layer: The zirconium and aluminum dual-doped ternary cathode material prepared in step 1) is mixed with ethylene glycol (CH2OH)2 and stirred continuously, and the resulting solution is transferred to a reaction kettle, heated, and kept warm to obtain a ternary cathode material with CQDs coated on the surface; 3) Preparation of nano-CaCO3 coating layer: After uniformly mixing the product obtained in step 2) with nano-CaCO3, the mixture is sintered in an oxygen atmosphere to obtain a ternary positive electrode material with a double-doping and double-coating structure.
4. The method according to claim 3, characterized in that In step 1), the molecular formula of the ternary precursor is: Ni 0.7 Co 0.1 Mn 0.2 (OH)2; The amount of zirconium added is 0.1%-0.3% of the mass of the ternary precursor; The amount of aluminum added is 0.05%-0.15% of the mass of the ternary precursor; The ratio of the total molar number of metals in the ternary precursor to the molar number of Li in lithium carbonate is 1:1.02-1.
069.
5. The method according to claim 3, characterized in that: In step 1), the sintering condition is 900-930°C and the time is 10-20h; During the sintering process, oxygen with a purity of more than 95% is introduced.
6. The method according to claim 3, characterized in that In step 2), the mass ratio of the ethylene glycol (CH2OH)2 to the zirconium and aluminum dual-doped ternary positive electrode material obtained in step 1) is: 1:2-6; The continuous stirring time is 1-3h; The heating temperature is 160-240℃ and the holding time is 4-6h; Step 2) also includes cooling the reaction system to room temperature after heat preservation, centrifuging, washing, and vacuum drying the precipitate, wherein the vacuum drying temperature is 100-120° C. and the time is 4-8 hours.
7. The method according to claim 3, characterized in that In step 3), the amount of the nano-CaCO3 added is 0.05-0.15% of the mass of the ternary positive electrode material obtained in step 2); The sintering temperature is 600-700°C and the sintering time is 4-6h; Step 3) also includes the operations of crushing, screening and demagnetizing the sintered product to obtain the final product.
8. Use of the ternary cathode material according to claim 1 or 2 in lithium-ion batteries.
9. A lithium ion battery, wherein the positive electrode of the lithium ion battery is made of the ternary positive electrode material according to claim 1 or 2.
10. An electrical device comprising the lithium-ion battery according to claim 9.
Citation Information
Patent Citations
Aluminum coated ternary zirconium-doped composite material, composite cathode material, preparation and application thereof in lithium ion batteries
CN108428862A
Positive pole piece and electrochemical device
CN111200111A
Positive pole piece and electrochemical device
CN111200112A
Coated ternary positive electrode material, preparation method thereof and lithium ion battery
CN112993259A
Lithium ion battery positive electrode material, preparation method thereof and lithium ion battery
CN113036105A